Gender phraseology in Kazakh - Kortabaeva, G. К.; Esimbekova, N. (Journal of Oriental Studies, 2016)
It is known that every language has a particular view of the world. In this picture the world is quite interesting parts are the gender and phraseological units. Gender phraseology compared languages is of interest not only in their own linguistic, and ethno-linguistic and in lingvokulturologicheskom aspects, therefore, characterized in comparative terms phraseological units provide new information on the characteristics of world perception, psycho-emotional and intellectual development of the world media of the language.